Regenerating agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Regenerating agriculture: policies and practice for sustainability end self-reliance by Jules Pretty 1995 320pp ISBN I 85383 198 0 (Pbk)